(untitled) (Research, Society and Development, 2021)
Sepsis can be defined as a systemic response to a specific infectious disease, whether caused by bacteria, viruses, fungi or protozoa. Being the leading cause of death in intensive care units (ICU). The study aimed to identify the clinical factors and factors related to death in patients hospitalized with sepsis in the Intensive Care Unit, involving patients diagnosed with COVID19 and patients who underwent invasive procedures using a catheter. It brought the understanding of how important early diagnosis is to reduce mortality in patients admitted to the ICU and the correct management with antimicrobials and risk factors for the worsening of sepsis. It is necessary that health professionals are aware of all signs and symptoms that precede the severe condition of sepsis. The study is based on articles published between 2015 and 2021 found on digital platforms LILACS (Latin American Literature in Science of Health), ACADEMIC GOOGLE and the SciElo electronic library (Scientific Electronic Library Online).